Tantangan Hukum dalam Pemanfaatan Maritime Autonomous Surface Ship (MASS) - A Indah Camelia; Athyra Elmilla (Media Iuris, 2022)
Technology development in the maritime industry led to the point where we now have unmanned ships run by automated systems. Therefore, (unmanned) crewless ships that were once only science fiction become real. Maritime Autonomous Surface Ships (MASS) have existed since world war two, and they develop by then. The existence of Maritime autonomous surface ships (MASS) has opened doors to new opportunities and enormous economic benefits for the maritime industry. Even though it will be run in automatic mode, the ship will still be monitored on land by the Shore Control Centre (SCC). This research will describe the aspects of definition, practice, the rule of law, and the use of MASS for seafarers and the maritime industry in general. While maritime regulation has not anticipated this magnitude before, thus not yet fully prepared to accommodate partially or fully automated ships. Consequently, A maritime legal regime still needs to ensure that MASS is safe and can be used sustainably.